Kadar Unsur Timbal pada Tanaman Kangkung di Tiga Pasar Tradisional Kecamatan Cilandak, Jakarta Selatan - Adila, Mirjani; Laz, Thamzil; Yunita, Etyn (Al-Kauniyah: Jurnal Biologi, 2014)
Water spinach (Ipomoea sp.) is a plant that is commonly consumed by the public. Shifting cultivation, distribution and sales that are not protectedÂ make vegetables easily contaminated by pollutants in the environment, one of the lead element. This study was conducted to determine the element content of Pb in water spinach sold in three traditional markets Cilandak subdistrict, South Jakarta. This study was conducted from February-March 2014 by using Atomic Absorption Spectrophotometer instrument (AAS) method flame. Analysis of the data using Analysis of Variance (ANOVA) with a confidence level of 95 %. If there are any differences, then followed by Duncan's Multiple Range Test. The Maximum Tolerable Intake (MTI) test to determine the maximal consumption of watercress with a particular assay with an approximate weight of 60 kg. Based on this research, the element content of lead in water spinach in three traditional markets District of Cilandak ranged from 1.22 to 22.06 mg/kg. No significant effect on the three traditional markets District of Cilandak location. Organ roots have high levels of lead element compared to levels in the leaves and stems. The entire test sample had levels of lead element above SNI 7387:2009 maximum threshold of 0.5 mg/kg so They are not safe for consumption. Average maximum weight of kale on the three traditional markets in Sub Cilandak that may be consumed per week in the organs of leaves and stems ranged from 0.1492 to 0.6032 kg.